PENILAIAN SUPERVISOR JASA KONSTRUKSI TERHADAP PENGUASAAN ILMU KUANTITI SURVEYING MAHASISWA TEKNIK SIPIL FT-UNP YANG MELAKSANAKAN PENGALAMAN LAPANGAN INDUSTRI (PLI) DI KOTA PADANG - 460-467 , Andi Putra Halomoan (Universitas Negeri Padang, 2015)
ABSTRACT The background of this research was the complaint from construction companyon the performance of students into implement the field industrion practice.Therefore, the aim oft his study was toreveal the construction supervisor assessment of the quantit surveying mastery to student of civil engineering faculty of Padang State University. This research was quantitative descriptive.The population of this study was the supervisor construction services at the field of student industrion practicein Padang totaling 10 companies. Techniquesin data collection by using the question naireby Likert scale Data were analyzed by using the mean percentage and mean formula. The results showed that the construction supervisor assessment of the mastery of quantity surveying students ofcivil engineering faculty of Padang State Universitywhich carry field industrion practice in four indicators: Calculating Volume, Calculating Weights achievement, Counting Materials Needed and Counting Labor which takes. Based on the degree of achievement it can be considered sufficient. Overall assessment of the construction supervisors quantity surveying ofcivil engineering faculty of Padang State Universitywhich carry field industrion practice in Padang reached the achievement of 59.94% and the category enough. Keywords: assessment, quantitysurveying,constraction service